Laparoscopic hysterectomy as a treatment modality for gestational trophoblastic neoplasms: a report of two cases - Rakić, Aleksandar; Jokanovic, Predrag (Vojnosanitetski pregled, 2022)
Introduction. Measuring the serum levels of human chorionic gonadotropin beta isoform (β-hCG) remains a crucial marker for diagnosing gestational trophoblastic neoplasms (GTNs). Choriocarcinoma is commonly diagnosed due to extremely high levels of β-hCG, but the presence of distant metastasis is not uncommon. Placental site trophoblastic tumors and epithelioid trophoblastic tumors remain an enigma because the levels of β-hCG are usually low. Case report. The first case report describes a 44-year-old woman, P2G3, admitted to the Clinic under the suspicion of molar pregnancy. She had vaginal bleeding with variable intensity, and her β-hCG was 1,837,787 mIU/mL. After two explorative curettages, the level of β-hCG declined, and a partial hydatidiform mole (HM) was diagnosed histopathologically. The patient was admitted to the Clinic on two occasions due to the increasing values of β-hCG. Since β-hCG failed to drop after two explorative curettages, a hysteroscopic biopsy, and one chemotherapy cycle, along with the suspicious ultrasonographic feature of metastatic GTN, and the fact that the patient has refused further chemotherapy, a total laparoscopic hysterectomy was performed. Choriocarcinoma was diagnosed after a histopathological exam was done. The second patient, a 50-year-old woman, P2G4, was admitted to the Clinic under the ultrasonographic suspicion of molar pregnancy. She was complaining of pelvic discomfort and frequent urination. Initial levels of β-hCG were 128,359 mIU/mL. Instrumental revision of the uterine cavity was performed, and partial HM was diagnosed histopathologically. Because of the increasing levels of β-hCG, ultrasonographical suspicion of the development of GTN in the uterine corpus, in accordance with the patient’s age and the fact that she has regular menstrual cycles, total laparoscopic hysterectomy was performed, and a histopathological exam made the diagnosis of the placental site trophoblastic tumor. Conclusion. Laparoscopic hysterectomy could be a treatment of choice for the chemotherapy-resistant GTNs but also for choriocarcinoma in patients who have finished their reproductive activity and refuse to be treated with chemotherapeutics.